Australian family day care educators' experiences of supporting children's mental health, and their own mental health and wellbeing. Issue 2 (June 2022) - McGuffog, Romany; Fitzgeraldson, Elloyse; Lyford, Bronte; Triandafilidis, Zoi; Fitzpatrick, Sally; Hazel, Gavin
This mixed-methods study explored (1) family day care (FDC) educators' confidence and capability to support children's mental health, and (2) assessed their own mental health and wellbeing. Descriptive analysis of the survey ( n = 144) highlighted that most participants were in the normal range for mental health and wellbeing; however, identifying mental ill-health in children, access to resources and awareness of support services were areas where participants were less likely to feel confident or capable. In the interviews ( n = 14), three themes were identified in the interviews for the first research question (including the central role of the FDC educator, lack of training and resources and limited professional support) and three themes were identified for the second research question (the importance of mental health for educators, being a small business owner and connecting with other educators). The results highlighted a need for additional support and resources for educators specifically targeting the mental health and wellbeing of children.